2020
DOI: 10.1111/tpj.14710
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐specific study across the stem of Taxus media identifies a phloem‐specific TmMYB3 involved in the transcriptional regulation of paclitaxel biosynthesis

Abstract: SummaryTaxus stem barks can be used for extraction of paclitaxel. However, the composition of taxoids across the whole stem and the stem tissue‐specificity of paclitaxel biosynthesis‐related enzymes remain largely unknown. We used cultivated Taxus media trees for analyses of the chemical composition and protein of major stem tissues by an integrated metabolomic and proteomic approach, and the role of TmMYB3 in paclitaxel biosynthesis was investigated. The metabolomic landscape analysis showed differences in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…The TMT-labeled peptide solution was separated by a Pierce™ High pH Reversed Phase Peptide Fractionation column on an Agilent high-performance liquid chromatographer (HPLC) system. Thirty fractions were harvested for each sample and concatenated to 15 fractions for further analysis (Yu et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The TMT-labeled peptide solution was separated by a Pierce™ High pH Reversed Phase Peptide Fractionation column on an Agilent high-performance liquid chromatographer (HPLC) system. Thirty fractions were harvested for each sample and concatenated to 15 fractions for further analysis (Yu et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies have shown that jasmonates, gibberellin, auxin and ethylene are involved in the regulation of paclitaxel biosynthesis to maintain a delicate balance between growth and defence in Taxus [16][17][18] . Several transcription factors (TFs), including AP2/ERF, WRKY, MYC and MYB, have been found to regulate the expression of paclitaxel biosynthetic genes [19][20][21] . However, the comprehensive regulatory mechanisms underlying the growth-defence trade-off are still poorly understood.…”
mentioning
confidence: 99%
“…Differenially expressed MYC TFs might play an important role in taxol biosynthesis. Interestingly, a phloemspecific TmMYB3 was reported to be involved in the transcriptional regulation of paclitaxel biosynthesis [55]. Recently, expression profiling and posttranscriptional regulation of the R2R3-MYB TF family in T. chinensis have been well analyzed [56].…”
Section: Discussionmentioning
confidence: 99%